RACK1 promotes the development and function of alveolar macrophages through directly binding to and stabilizing PPARγ - Hui Jiang; Hongfang Yun; Xu Wang; Zhuo Shen; Genyu Liu; Tao Zou; Tingting Guo; Mengyao Wu; Yuchen Lu; Lijiao Deng; Ju Miao; Hongbin Deng; et al. (Proceedings of the National Academy of Sciences, 2025)
Alveolar macrophages (AMs) are indispensable to prevent pulmonary alveolar proteinosis and clear inhaled pathogens. Receptor for activated C kinase 1 (RACK1) is a versatile adaptor protein that regulates multiple signaling pathways. Whether RACK1 is implicated in AM alterations remains elusive. Alveolar type 2 cells-derived granulocyte-macrophage colony-stimulating factor and autocrine transforming growth factor-β1 drive the transcription of Pparg , the gene encoding AM signature transcription factor peroxisome proliferator-activated receptor-γ (PPARγ). The regulation of PPARγ stability during AM development and maintenance remains unexplored. Here, we report that myeloid RACK1 deficiency results in the scarcity of mature AMs and pulmonary alveolar proteinosis. A mixed bone marrow chimera approach reveals a cell-intrinsic role of RACK1 in AM differentiation. Bulk RNA-sequencing indicates a considerable loss of AM identity, impaired PPAR signaling, but a largely unchanged Pparg messenger RNA (mRNA) level in the absence of RACK1. Indeed, myeloid deletion of Rack1 halts AM differentiation in vivo and blocks the ability of PPARγ agonist to induce AM-like cells in vitro. Mechanistically, RACK1 directly binds to and stabilizes PPARγ by preventing its ubiquitination and degradation. Moreover, myeloid RACK1 deficiency renders mice susceptible to Streptococcus pneumoniae infection.